An anthracenecarboximide-guanidine fluorescent probe for selective detection of glyoxals under weak acidic conditions. Issue 15 (25th March 2022) - Chen, Junwei; Lin, Yuna; Xing, Wanjin; Zhang, Xingchen; Xu, Huan; Wang, Wei; Lou, Kaiyan
Abstract : Formation of 5-membered dihydroxyimidazolidines with increased deprotonation at around pH 6.0 and enhanced intramolecular charge transfer for turn-on fluorescence detection of glyoxals. Abstract : An anthracenecarboximide-guanidine based turn-on fluorescent probe ANC-DCP-1 for selective detection of glyoxals (methylglyoxal and glyoxal, GOS) over formaldehyde under weak acidic conditions around pH 6.0 was reported. The probe showed great potential in studying relative GOS levels in weak acidic biological fluids such as in urine for diabetic diagnosis and prognosis, and also found application in the food industry such as for fast unique manuka factor (UMF) scale determination of Manuka honey.